Syngas production from Gasification of Oil Palm Fronds with an Updraft Gasifier - Konda, R.E. (2012)
In present study, gasification of oil palm fronds (OPF) is performed in a pilot-scale updraft gasifier. Gasification experiments were conducted at atmospheric pressure using air as oxidizing agent. The effects of equivalence ratio on temperature profile, gas composition and gas calorific value are studied. The equivalence ratios employed in this study are 0.18, 0.22, 0.29, 0.35 and 0.4. The results showed that the amount of combustible gases, which are H2, CO and CH4 was found to be in the range of 16.79 – 33.9% of the total produced gases, and the average composition of the syngas at an optimum equivalence ratio of 0.29 was found to be 20.10% CO, 10.41% CO2, 1.20% CH4 and 6.60% H2 with an average calorific value of 4.42 and 4.62 MJ/Nm3 as low heating value (LHV) and higher heating value (HHV). While the maximum molar ratios of H2/CO and CO/CO2 was found to be 0.3 and 2.51 respectively.